Fabrication of an Ultrathin PMMA Foil for Sensing Applications in Microfluidic Systems - Rafael Ecker; Tina Mitteramskogler; Andreas Fuchsluger; Bernhard Jakoby (Proceedings)
This research work focuses on the fabrication of ultrathin polymethylmethacrylate (PMMA) foils using a spin coating process of in anisole dissolved PMMA on a water-soluble polyvinyl alcohol (PVA) foil. Currently, layer thicknesses as low as 1 µm can be achieved and even thinner layers appear to be possible. Sensors and actuators can be applied to the foils and directly integrated into the center of the channel of a polymer-based microfluidic chip. Specifically, the foil acts as a supporting structure that helps to position the sensor in the center of the channel. Thermal sensors, in particular, benefit from the low heat capacity of the foil. This will improve the performance and the accuracy of these sensors of which the impact on the fluidic flow is minimized.